2016
DOI: 10.17073/1997-308x-2016-3-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Mechanical Properties of Products Manufactured Using Selective Laser Melting of Powdered Materials

Abstract: Рассмотрены причины возникновения анизотропии свойств в изделиях, изготавливаемых по технологии селективного лазерного плавления металлических порошковых материалов. Представлены результаты оценки механических свойств образцов из сплавов основе титана Ti-6Al-4V, ВТ6 и жаропрочного никелевого сплава Inconel 718 в различных направ-лениях. Исследована микроструктура компактных образцов, полученных селективным лазерным плавлением. Приведе-на зависимость их механических свойств от ориентации заготовок относительно … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the SLM-produced parts, in addition to the speci c structure, defects may be present -mainly voids and lack of fusion [54]. Although no voids and microcracks were detected on the sample surface by optical microscopy, in [8,26] it is reported that porosity is actually very common in SLM-produced parts.…”
Section: Initial Microstructure Of Slm-produced and Wrought Ti-6al-4vmentioning
confidence: 99%
“…In the SLM-produced parts, in addition to the speci c structure, defects may be present -mainly voids and lack of fusion [54]. Although no voids and microcracks were detected on the sample surface by optical microscopy, in [8,26] it is reported that porosity is actually very common in SLM-produced parts.…”
Section: Initial Microstructure Of Slm-produced and Wrought Ti-6al-4vmentioning
confidence: 99%
“…Products from titanium alloys are manufactured using both selective laser melting (SLM) [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and laser metal deposition (LMD) [25][26][27] technologies.…”
Section: Introductionmentioning
confidence: 99%
“…These findings point out that there is no transverse anisotropy induced by the resulting irregular geometry. Thus, any potential anisotropy in the final material would be resulting from the anisotropic microstructure produced by the SLM process [208].…”
Section: Influence Of Manufacturing Irregularitiesmentioning
confidence: 99%